Reduction of the severity of apple bitter rot by fruit immersion in chitosan - Felipini, Ricardo Barbosa; Di Piero, Robson Marcelo (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to evaluate the aplication of chitosan on the control of apple bitter rot in postharvest conditions and its effects on Colletotrichum acutatum and fruit peroxidase activity. Apple fruit previously infected with the pathogen were immersed in chitosan suspensions with different concentrations and pHs. To study some possible action mechanisms, in vitro tests were carried out to evaluate the effect of chitosan on spore germination and mycelial growth of C. acutatum. The capacity of chitosan to induce the synthesis of defense enzymes (peroxidases) was evaluated in fruits by spectrofotometric assay. Different doses and pH of chitosan were found to be effective in the reduction of the disease severity. Chitosan at 10 g L-1 (pH 4) had the most technical viability for the control of the disease and reduced the severity in 26%. Considering the action mechanisms, chitosan did not increase peroxidase activity in the fruits; however, it reduced both spore germination and mycelial growth of the pathogen. Chitosan applied at postharvest is an alternative to reduce bitter rot severity.